Analysis of volatile organic compounds of bacterial origin in chronic gastrointestinal diseases - Walton, Christopher; Fowler, Dawn P.; Turner, Claire; Jia, W.; Whitehead, Rebekah N.; Griffiths, Lesley; Dawson, Claire; Waring, Rosemary H.; Ramsden, David B.; Cole, Jeffrey A.; Cauchi, Michael; Bessant, Conrad M.; et al. (Wiley, 2013)
BACKGROUND: The aim of this study was to determine whether volatile organic compounds (VOCs) present in the headspace of feces could be used to diagnose or distinguish between chronic diseases of the gastrointestinal tract and apparently healthy volunteers. METHODS: A total of 87 people were recruited, divided between 4 categories: healthy volunteers (n = 19), Crohn's disease (n = 22), ulcerative colitis (n = 20), and irritable bowel syndrome (n = 26). They each supplied fecal samples before, and except for the healthy volunteers, after treatment. Fecal samples were incubated in a sample bag with added purified air at 40°C and headspace samples were taken and concentrated on thermal sorption tubes. Gas chromatography-mass spectrometry then desorbed and analyzed these. The concentrations of a selection of high-abundance compounds were determined and assessed for differences in concentration between the groups. RESULTS: Crohn's disease samples showed significant elevations in the concentrations of ester and alcohol derivates of short-chain fatty acids and indole compared with the other groups; indole and phenol were elevated in ulcerative colitis and irritable bowel syndrome but not at a statistically significant level. After treatment, the levels of many of the VOCs were significantly reduced and were more similar to those concentrations in healthy controls. CONCLUSIONS: The abundance of a number of VOCs in feces differs markedly between Crohn's disease and other gastrointestinal conditions. Following treatment, the VOC profile is altered to more closely resemble that of healthy volunteers.